Crocin exerts anti-inflammatory and anti-arthritic effects on type II collagen-induced arthritis in rats. (1st January 2018) - Liu, Wei; Sun, Yufeng; Cheng, Zhenping; Guo, Yong; Liu, Peiming; Wen, Ying
Abstract: Context: Rheumatoid arthritis (RA) is a common systemic auto-immune disease, which is characterized by chronic and symmetry synovial inflammation. Crocin has been reported to exhibit anti-inflammatory effects in animal models. Objective: This study investigates the anti-inflammatory and anti-arthritic effects of crocin on type II collagen-induced arthritis (CIA) in Wistar rats. Materials and methods: The CIA rat model was established and randomly divided into five groups with or without crocin treatment (10, 20 or 40 mg/kg), which was started on day 21 after arthritis induction and persisted for 36 days. The symptoms and molecular mechanisms of CIA and crocin-treated CIA rats were compared and investigated. Results: CIA rats presented severe RA symptoms, including high arthritis score, paw swelling, joint inflammation, bone erosion, chondrocyte death, cartilage destruction, enhanced expressions of matrix metalloproteinase (MMP) and pro-inflammatory cytokines. However, crocin could mitigate these symptoms. Crocin (40 mg/kg) exhibited the most efficient therapeutic function on CIA rats: the histological scores of joint inflammation, bone erosion, chondrocyte death, cartilage surface erosion, and bone erosion of CIA rats receiving 40 mg/kg crocin treatment were comparable to the normal rats. MMP-1, -3 and -13 protein expression levels of CIA rats with 40 mg/kg crocin treatment were decreased to levels similar to normal rats. Moreover, crocin could also inhibit the expression of TNF-α, IL-17, IL-6 and CXCL8 in serum and ankle tissues of CIA rats. Conclusions: In summary, crocin exhibits therapeutic potential for RA, by mitigating the symptoms and inhibiting the pro-inflammatory factor expression.